2022
DOI: 10.20471/acc.2022.61.s2.13
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Pain and Therapy

Abstract: Pain is the commonest presenting feature that leads to a diagnosis of cancer and remains the most feared symptom by patients throughout the course of the disease. Beuken-van Everdingen showed that pain prevalence rises with disease progression and affect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Un opioide potente sigue siendo el fármaco de elección para tratar el dolor moderado o intenso en pacientes con cáncer avanzado. Las investigaciones futuras deberían centrarse en definir la eficacia de los AINE, los antidepresivos, los anticonvulsivos, los corticosteroides y el posible papel de los enfoques no farmacológicos en el tratamiento del dolor en pacientes con cáncer avanzado (Brozović et al, 2022).…”
Section: Dolorunclassified
“…Un opioide potente sigue siendo el fármaco de elección para tratar el dolor moderado o intenso en pacientes con cáncer avanzado. Las investigaciones futuras deberían centrarse en definir la eficacia de los AINE, los antidepresivos, los anticonvulsivos, los corticosteroides y el posible papel de los enfoques no farmacológicos en el tratamiento del dolor en pacientes con cáncer avanzado (Brozović et al, 2022).…”
Section: Dolorunclassified
“…Consequently, paracetamol and non-steroidal anti-inflammatory drugs (NSAIDs) are employed to address mild pain in patients, whereas mild and potent opioids such as codeine, tramadol, and morphine are utilized for the management of moderate to severe pain (61,62). Accurately defining the type of cancer pain that a patient is experiencing is crucial, as it may necessitate the implementation of additional strategies like adjuvant analgesia (using antiepileptic or antidepressant drugs), corticosteroids, radiotherapy, and interventional procedures (63). For instance, neuropathic pain can be partially treated by combining opioids with antiepileptic or antidepressant drugs (64,65).…”
Section: Is a Tumor Always Painful And What Is Exactly Cancer Pain?mentioning
confidence: 99%
“…It has been reported that commonly used radiotherapy techniques can improve the tumor microenvironment (TME) to some extent [21,22] . However, radiotherapy treatment for prostate cancer commonly results in unavoidable adverse side effects, including lower urinary tract symptoms, intestinal complications, erectile dysfunction, and myelosuppression, which limits the application of radiotherapy in patients [23] . In the previous study, we reported that radiated tumor cell-derived microparticles (RMPs) are the main medium of the bystander effect induced by radiotherapy [24] .…”
Section: Introductionmentioning
confidence: 99%